ERCP in babies: Low risk of post-ERCP pancreatitis – results from a multicentre survey. Issue 1 (February 2020) - Goetz, Martin; Andersen, Philipp; Bergman, Jacques; Frei, Nicola; Schmidt, Arthur; Kähler, Georg; Martus, Peter; Dechêne, Alexander
Background and aims: Endoscopic retrograde cholangiopancreatography (ERCP) is rarely performed in newborns, and the risk of post-ERCP pancreatitis (PEP) has not been defined in this age group. We therefore performed a European multicentre analysis of PEP rates and risk factors in children aged ≤1 year. Patients and methods: Based on a sample size estimation, 135 consecutive ERCPs in 126 children aged ≤1 year were evaluated from five European centres, and the first ERCP per child analysed. All ERCPs and clinical reports were reviewed manually for PEP and associated risk factors. All ERCPs were performed by endoscopists with high ERCP expertise. Results: No PEP was observed (0/126, 0.0%, CI 0–2.9%) despite the formal presence of multiple risk factors and despite lack of PEP prophylaxis (except one patient having received a pancreatic duct stent). The PEP rate was significantly lower than the PEP rate expected in adults with similar risk factors. Conclusions: ERCP in children aged ≤1 year is safe in terms of PEP. The PEP risk is significantly lower in children aged ≤1 year than in adults, therefore no PEP prophylaxis seems to be needed in young children. Risk factors from adults may not apply to children under 1 year. Reluctance to perform diagnostic ERCP in suspected biliary anomalies should not be based on presumed PEP risk.